Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/foods12061242
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Food Safety: A Decade Review and Bibliometric Analysis

Abstract: Artificial Intelligence (AI) technologies have been powerful solutions used to improve food yield, quality, and nutrition, increase safety and traceability while decreasing resource consumption, and eliminate food waste. Compared with several qualitative reviews on AI in food safety, we conducted an in-depth quantitative and systematic review based on the Core Collection database of WoS (Web of Science). To discover the historical trajectory and identify future trends, we analysed the literature concerning AI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 205 publications
1
10
0
Order By: Relevance
“…The largest cluster of journals was led by Food Chemistry with the highest numbers of publications. This preriqucites correspond with 53 [ 53 ] in the bibliometric analysis of food safety using artificial intelligence (AI). Food Chemistry is one of the most productive journals in this research section aforementioned in Table 1 .…”
Section: Discussionsupporting
confidence: 70%
“…The largest cluster of journals was led by Food Chemistry with the highest numbers of publications. This preriqucites correspond with 53 [ 53 ] in the bibliometric analysis of food safety using artificial intelligence (AI). Food Chemistry is one of the most productive journals in this research section aforementioned in Table 1 .…”
Section: Discussionsupporting
confidence: 70%
“…Food safety systems are deployed to monitor food production, processing, and distribution to prevent foodborne illnesses. These systems track outbreaks of foodborne illness and identify the sources of contamination, allowing officials to take action to prevent future outbreaks [103].…”
Section: Food Safetymentioning
confidence: 99%
“…A study of 35 US peanut cultivars using antisera from allergic patients also found no significant variation (Dodo et al., 2002; Isleib & Wynne., 1992). However, rapid and easy phenotyping methods for different allergens are required to increase the efficiency of breeding reduced allergen crops (Liu et al., 2023).…”
Section: Phenomics and Omics Approaches To Reducing Allergensmentioning
confidence: 99%
“…Traditional methods for identifying food allergens mostly rely on in vivo and in vitro experiments, which can be time consuming and uneconomical. However, artificial intelligence (AI) and bioinformatics have the potential to significantly reduce plant food allergens by aiding in the identification of specific allergenic proteins in plants as well as the development of novel methods to modify or remove allergens from food products (Liu et al., 2023). AI in allergy and immunology has various potential therapeutic applications ranging from disease diagnosis to multidimensional data reduction in electronic health records or immunologic datasets (Khoury et al., 2022).…”
Section: Phenomics and Omics Approaches To Reducing Allergensmentioning
confidence: 99%